Public Innovation Funding for the Green Transition : Evidence from Business Finland - Joensuu, Mikaela (My University, 2025)
This study investigates how Business Finland's innovation funding has supported Finland's green transition between 2000 and 2025. Using a keyword-based method rooted in climate and sustainability discourses, the analysis maps the volume, structure, and thematic orientation of funded RDI projects. The results show climate-related funding has consistently increased throughout the 2000s, with a significant rise in project share since 2019. The study indicates that over 75% of funding from 2022 to 2024 will likely be directed toward green transition initiatives. This shift supports national policy goals that became more prominent under the Sanna Marin government. However, the relatively stagnant share of program-linked projects may suggest that Business Finland’s funding has aligned more with firms’ bottom-up interests than with a coordinated or directive policy agenda. The analysis also highlights large firms' dominant role in total funding volume. Medium-sized companies continue to receive a relatively small share of funding, reflecting broader patterns in Business Finland’s overall allocation practices. When examined by sector, scientific research and development dominate funding distribution, suggesting that many green transition efforts remain in early-stage research rather than in commercially mature applications. Findings may partly explain Finland's weak productivity trends if investments focus on emerging themes that are still in the invention stage, and firms cannot fully leverage them in their business activities. The green transition requires substantial investments over several years before firms can expect significant commercial benefits. While the findings based on keyword analysis suggest alignment with mission-oriented policy goals, it remains unclear to what extent the funded projects have substantively contributed to sustainability outcomes. The keyword-based approach identifies thematic associations but does not capture the depth, effectiveness, or practical implementation of green objectives. As such, further research is needed to assess whether these projects have genuinely advanced the green transition or merely adopted climate-related language at a superficial level. A more in-depth assessment of project outcomes, policy tools, and the broader innovation ecosystem is needed to better understand how effectively public funding supports Finland’s green transition.
Keywords: green transition, public RDI funding, innovation policy, Business Finland, sustainability